Risk Management of the Joint Partnership Pattern: Case Study of Shrimp Farming in Indonesia - Barusman, M. Yusuf S.; Gultom, Indriati Agustina; Redaputri, Appin Purisky (International Review of Management and Marketing, 2019)
Risk management in farming business is an important point in dealing with various business problems, especially crop failure. This paper focuses on risk management strategy, institutional model and analysis of the partnership pattern of shrimp farming business. Using the case study methodology, the data collected through literature study, field observation, in-depth interview and focus group discussion (FGD) with resource persons acting as representatives of the parties involved in Bumi Dipasena. The management of vaname shrimp farming business in Bumi Dipasena uses a Joint Business Partnership Pattern. This Joint Business Partnership Pattern is a form of business management innovation with its own institutional model. Several unique features of the Joint Business Partnership Pattern are currently being implemented, namely, the existence of a profit-sharing pattern, the concept of business risk reserve and the concept of 1,000 rupiah and emergency debt. These three processes are business risk management strategies. Keywords: Risk Management Strategy; Institutional Model; Partnership Pattern; Business Management Innovation JEL Classifications: D81, M21, O30 DOI: https://doi.org/10.32479/irmm.7390